Sittlichkeit and Baukunst “as” second nature. The philosophy of Hegelian architecture and the building as external interiority of an ethical bond - Cavalleri, Matteo (Itinerari, 2024)
The essay draws a relationship between the dwelling dimension of Hegel’s Sittlichkeit and the philosophy of architecture presented in the Aesthetics, both of which are seen as spiritual expressions of second nature. Central to the analysis is the consideration of the building – analysed in its historical conceptual evolution – as a place of self-knowledge for the spirit, which is expressed through a continuous modification of the relationship between internality and externality. A topicality within which the aesthetic representation of an ethical bond that supports the emergence of Einzelheit is highlighted.